How do coastal residents perceive past and future changes in a Mediterranean lagoon ecosystem services?. (1st May 2023) - Derolez, Valérie; Mongruel, Rémi; Adjeroud, Fériel; Rey-Valette, Hélène; Nicolle, Dorian; Lautrédou-Audouy, Nicole
Abstract: Coastal ecosystems provide a wide range of ecosystem services (ES) subject to strong human pressure and are included in conservation policies that aim to increase their resilience. Implementing resilience measures requires knowledge of the public perceptions of social-ecological systems so that commitment to environmental protection may be enhanced. Few studies address public perception of the evolution of social-ecological systems and integrate the diversity of ES (regulating, provisioning and cultural). This article is based on a survey of 476 inhabitants and deals with their perceptions of past (50 years) and future (+15 years) ES. It focuses on the Thau lagoon (French Mediterranean) that offers many ES and where managers prioritize traditional uses such as shellfish farming and fishing. Respondents' answers were compared with the results of scientists' and experts' evaluations to assess the level of public knowledge. The results indicate consistency in the qualitative and quantitative responses of local residents concerning the long-term evolution of ES and show them to have a fairly sound knowledge. However, there are some differences in trends with substantial variation for several ES probably related to judgement or anchoring biases. Furthermore, a majority of local residents had a mixed perception of local structuring ES. This innovative approach to the perceptions of ES momentum suggests that improved conservation policies must: (i) take into account the different communication and awareness requirements of people and (ii) integrate local knowledge through dialogue. Highlights: Assessment of the coastal residents perception of past and future ecosystem services representative of coastal lagoons. The coastal residents survey show a fairly sound knowledge of the long-term evolution of ecosystem services (ES). Coastal residents perceived differences only between the past two periods and the current period. Residents' qualitative and quantitative responses on long-term trend were consistent for 5 out of the 8 ES studied. Most coastal residents considered diversified ES to be important, with a slight fall in future projections.